2014
DOI: 10.2196/mhealth.3120
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Use of Smartphones for Learning Purposes by Australian Dental Students

Abstract: BackgroundMobile Internet devices and smartphones have at present a significant potential as learning tools and the development of educational interventions based on smartphones have attracted increasing attention.ObjectiveThe objective of this study was to obtain a deeper insight in the nature of students’ use of smartphones, as well as their attitudes towards educational use of mobile devices in order to design successful teaching interventions.MethodA questionnaire was designed, aiming to investigate the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 28 publications
10
66
1
10
Order By: Relevance
“…Present study findings showed that 68% of dental and 70.45% of medical doctors are using health care apps on their smart phone. These results are in accordance with the previous studies 21,22 . This suggests that it is a global trend and practice for health care professionals to own a smart device and use medical apps to support their study and clinical sessions.…”
Section: Discussionsupporting
confidence: 94%
“…Present study findings showed that 68% of dental and 70.45% of medical doctors are using health care apps on their smart phone. These results are in accordance with the previous studies 21,22 . This suggests that it is a global trend and practice for health care professionals to own a smart device and use medical apps to support their study and clinical sessions.…”
Section: Discussionsupporting
confidence: 94%
“…Many studies such as [3,4,5,6,7] have been conducted on assessing the use and effects of smartphones especially for learning purposes. For example, reference [3] and [4] reported on the nature of students' use of smartphones, as well as their attitudes towards utilizing smartphones for educational use, while [5,6,7] reported that smartphones have negatively effects on a learning process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, reference [3] and [4] reported on the nature of students' use of smartphones, as well as their attitudes towards utilizing smartphones for educational use, while [5,6,7] reported that smartphones have negatively effects on a learning process.…”
Section: Introductionmentioning
confidence: 99%
“…These technologies were not included everywhere in the formal curriculum, but some authors underline the opportunity to design adequate educational methods, activities and material (Oulasvirta et al, 2012;Rung et al, 2014).…”
Section: Implications For the School Environmentmentioning
confidence: 99%